Behavior of mortar blended with quartzite residues when subjected to natural aging - Barros, Sâmea Valensca Alves; Dantas, Gerbeson Carlos Batista; Silva, António Santos; Neves, Gelmires de Araújo; Menezes, Romualdo Rodrigues; Brito, André Luiz Fiquene de; Pimentel, Patrícia Mendonça; Melo, Stefeson Bezerra De (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The mixture of mortars with quartzite residues is a recycling technique that has been widely used to promote the adequate management of solid waste generated in the municipality of Várzea-PB, Brazil. However, there are no reports in the literature that prove the durability of the mortar mixed with these residues when subjected to environmental conditions over time. Thus, the present work has as objective to study the durability of mortars incorporated with quartzite residues when submitted to natural aging. The reference mortar and incorporated with quartzite were prepared according to NBR 13281 and submitted to natural aging for 28, 60, 120, 180 and 360 days. Then, they were characterized by x-ray diffraction, thermogravimetric analysis and simple compression strength and carbonation and pozzolanic measurements. The results showed that, despite the decrease in compressive strength of quartzite containing mortars, the durability was not compromised, since the values were maintained in the range suggested by NBR 13281. Finally, it was concluded that mortars produced with quartzite residues presented good mechanical behavior when submitted to natural aging.